Effectivity of Antihypertensive Drugs Use in Pregnant Woman with Diagnoses of Preeclampsia Hospitalized at Abdoel Wahab Sjahranie Hospital and Inche Abdoel Moeis Hospital Samarinda City: Efektivitas Penggunaan Obat Antihipertensi Pada Ibu Hamil dengan Diagnosa Preeklampsia Rawat Inap di RSUD Abdoel Wahab Sjahranie dan RSUD Inche Abdoel Moeis Kota Samarinda - Difta, Rismania Shita; Mus, Nurul Muhlisa; Almeida, Maria; Herman, Herman (Jurnal Riseta Naturafarm, 2025)
The use of appropriate and effective antihypertensive drugs is needed so that blood pressure in preeclampsia patients can be controlled so as not to endanger the condition of the mother and fe-tus. This study aims to determine the rationality and effectiveness of the use of antihypertensive drugs at RSUD Abdoel Wahab Sjahranie and RSUD Inche Abdoel Moeis in the period January 2022 - December 2023 which was carried out through retrospective data observation of hospital-ized patients with a total of 12 samples (RSUD Abdoel Wahab Sjahranie) and 10 samples (RSUD Inche Abdoel Moeis). The results of the evaluation of the rationality of antihypertensive drugs used were assessed as appropriate patients, appropriate indications, appropriate drugs, ap-propriate doses and appropriate time intervals of administration each by 100% based on the 2016 POGI guideline, Hospital Formulary, 2023 SOMANZ guideline, 2021 ISSHP guideline, and 2019 ACOG guideline. The effectiveness of using Methyldopa monotherapy showed better blood pressure reduction results (34.81/12.37 mmHg) than Nifedipine (21.41/5.6 mmHg), while the combination of Nifedipine and Methyldopa showed greater results than monotherapy (38.5/15.2 mmHg).